Four factor analysis of variance of fibre diameter (Mongolian Journal of Agricultural Sciences, 2015)
As for the research methodology, we used sample of cashmere of goats, from some soums of Khentii province. We formulated the definition that is expressed by the values of different experiments of 4 factor analysis of variance. When we calculated, we used the formulation of 4 factor analysis of variance. Fibre diameter of goats of Khentii aimag that went under the research fluctuated between 13.70-18.10μm, average was 115.63±0.005μm; female goats' fibre diameter fluctuated between 13.7-18.10 μm and average was 15.66±0.13 μm; while male goats' fibre diameter fluctuated between 13.8-17.40 μm and average was 15.60±0.005 μm. Fibre length of goats that went under the research fluctuated between 3.57-7.13μm; average was 5.13±0.004cm; female goats' fibre length fluctuated between 3.73-7.00cm and average was 5.01±0.005; while male goats' fibre length fluctuated between 3.57-7.13cm and average was5.23±0.004cm. In terms of the percentage of effects of each factor: the factor “Soum”'s effect percentage was 2.5%, and the effect percentage of the factor “Goat sex” was 1.23%, factor “Goat age” was 59.1%, and factor “Fibre length” was 20.14%, and factor “inter-reaction of all factors”'s effect percentage was 16.33%. Among these factors the strongest effect factor was the goat's age.Journal of agricultural sciences №15 (02): 159-165, 2015